Ultrastructural features of nerve fascicles and basal lamina abnormalities in Hirschsprung's disease - Wedel, Thilo; Holschneider, Alexander Matthias; Krammer, H. (European journal of pediatric surgery, 1999)
Although the pathogenesis of Hirschsprung's disease (HD) is not completely resolved, both the absence of nerve cells and the hypertrophy of nerve fascicles within the aganglionic colonic segment have been attributed to an abnormal intestinal microenvironment. Studies on animal models for HD revealed an altered ultrastructure of ingrowing nerve fascicles and abnormalities of basal laminae (BL). Therefore, the purpose of this study was to examine the ultrastructure of hypertrophied nerve fascicles in human HD with special reference to structural abnormalities of BL. Colonic specimens were obtained from patients with HD (n=10) and controls (n = 5) and processed for electron-microscopical examination. Hypertrophied nerve fascicles were characterized by a prominent perineural sheath surrounded by large amounts of collagen bundles, a collagen-filled endoneurium, vasa nervorum and abundant glial cells of extraenteric ultrastructure, which were arranged in mono- or oligoaxonal units and frequently displayed different stages of myelination. As these ultrastructural characteristics resembled typical features of extrinsic nerves and were similar to those observed in subserosal nerves, the prominent intramural nerve fascicles were considered to be of extraenteric origin. Most likely their overabundance contributes to the functional obstruction of the terminal colon. Morphological abnormalities of BL encountered in the aganglionic colonic segment consisted of an extensive multilamination of BL surrounding glial processes and an irregular thickening of BL surrounding perineurocytes and smooth muscle cells of the muscularis mucosae. Similar alterations in BL have also been described in inherited peripheral and diabetic autonomic neuropathies and attributed to reactivated Schwann cells. Thus, the overproduction of BL material within the hypertrophied nerve fascicles in HD may reflect an increased activity of proliferating glial cells. Since the smooth muscle cells of the muscularis mucosae showed abnormalities of BL similar to those observed in murine models for HD, it is suggestive that also in human HD the aganglionic colon is affected by a disturbed intestinal microenvironment impairing the neuronal colonisation and promoting the ingrowth of extrinsic nerves. The ultrastructurally observed alterations in BL of both neuronal and non-neuronal cells, as well as the increased amount of perineural and endoneural collagen provide further evidence that extracellular matrix components are abnormally distributed and overproduced within the bowel wall of patients affected by HD.